Assessing the association of sustainable agriculture with rural household food security (considering ecological, economic, and social aspects) - Sahraei, Salman; Pakravan-Charvadeh, Mohammad Reza; Gholamrezai, Saeed; Rahimian, Mehdi (Frontiers in Nutrition, 2022)
Due to the importance of sustainability in the world, we follow the missing pieces of the ‎puzzle of sustainable agriculture and food security as a huge gap in the literature. To ‎achieve this goal, a survey was analyzed to assess the linkage between these two concepts ‎in the rural areas in Lorestan province in Iran. The status of food security was assessed ‎using US Household Food Security Survey Module (HFSSM). A standard questionnaire ‎extracted from the related literature was applied to calculate sustainability indicators. The ‎results showed that the status of food security among households with no children (70%) was better ‎than those with one or more children (28%). According to the Tobit model, none of the ‎sustainability dimensions had a significant association with food insecurity. The results ‎support the fact that the assessment of agricultural sustainability at the microeconomic level, ‎short-term period, and a small, specified location cannot lead to reliable results due to ‎the similar behaviors of farmers in these areas. The low level of agricultural sustainability ‎is due to the lack of macroeconomic policies in the region to promote and disseminate ‎the principles of sustainability, lack of plans and actions to promote sustainability by ‎stakeholders and policymakers, and ignorance of the target community, as subsistence ‎producers who fall into a deprivation trap. The results suggest that policymakers should ‎use two short-term and long-term strategies to improve the level of agricultural ‎sustainability and increase food security status. ‎